Does Financial Literacy Improve Financial Inclusion? Cross Country Evidence - Theres Klühs; Antonia Grohmann; Lukas Menkhoff (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We study the effect of financial literacy on financial inclusion at the cross country level. Financial literacy is strongly related to higher financial inclusion (i.e. access and use of fin. services) and IV-regressions support a causal interpretation.Studying heterogeneous effects of financial literacy across countries shows that the marginal effect of financial literacy on financial inclusion is largest in countries with lower income, a less developed financial sector, and fewer bank branches.
Keywords: G21; O1; E44; 330